A Sentimental Journey Through France and Italy - Sterne, Laurence (Saga Egmont, 2022)
Set during the \'Seven Years War\' between England and France, \'A Sentimental Journey Through France and Italy\' was one of Sterne\'s last works. Seen as the epilogue to his \'Tristram Shandy\' books (later adapted for film, as \'A Cock and Bull Story´, starring Steve Coogan and Rob Brydon), it tells the tale of Yorick, as he travels between the two countries. While visiting Paris, Yorick is discovered to be without a passport. When he flees to Versailles in order to get one, he is mistaken for the jester in Shakespeare\'s \'Hamlet\'. Will he be able to escape imprisonment, or is the game up for our hero? A superb satire on another author\'s less-than-sentimental travelogue through the same countries.-